Análise in vivo das características biomecânicas de córneas normais e com ceratocone por meio da elastografia de coerência óptica - Stefano, Vinicius Silbiger de [UNIFESP] (2018)
Purpose: To assess depthdependent corneal biomechanical behavior in vivo in refractive surgery subjects using optical coherence elastography. Methods: A corneal elastography methodology based on a Fourierdomain optical coherence tomography was implemented in a clinical prototype. Low amplitude corneal deformation was produced during imaging with a linear actuatordriven lens coupled to force transducers. A crosscorrelation algorithm was applied to track framebyframe speckle displacement across horizontal meridian scans. Intrameasurement force and displacement data series were plotted against each other to produce an axial stiffness metric, k, defined by the firstorder term of a linear fit to the data. Elastographic maps displaying local k values across the cornea were generated, and the ratio of average axial stiffness for adjacent anterior and posterior stromal regions, ka/kp, was calculated. Intraclass correlation coefficients were used to estimate testretest reliability. The mean ka/kp values in normal and keratoconus patients were compared using the MannWhitney U test. Results: Twentyeight eyes were analyzed overall: 17 eyes from 10 normal patients and 11 eyes from 8 patients with keratoconus. The overall intraclass correlation was 0.907 (p < 0.01), indicating good testretest reliability. Graphs of force vs. displacement demonstrated that, for simultaneously acquired measurements involving the same applied force, anterior stromal displacements were lower (indicating stiffer behavior) than posterior stromal displacements in normal patients, with a mean ka/kp value of 1.123 ± 0.062. In keratoconus patients, this pattern is lost, with a mean ka/kp value of 1.003 ± 0.086, a significant difference (p < 0.01). Conclusion: Optical coherence elastography is a clinically feasible, noninvasive elasticity imaging method capable of resolving differences in depthdependent corneal biomechanical properties. Anterior stroma was stiffer in compression than the posterior stroma in normal patients, whereas ka/kp values were significantly lower in keratoconus, indicating a relative loss of native anterior stromal stiffness in the diseased corneas. This finding is consistent with histopathological evidence of Bowmanlevel abnormalities and regional loss of interlacing collagen fibrils in keratoconus. The clinical capability to measure these differences has important implications for refractive surgery screening and assessing the relative biomechanical impact of corneal refractive surgeries.